2014
DOI: 10.1160/th4-04-0383
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognosis of incidentally detected ambulatory atrial fibrillation

Abstract: SummaryIt was the aim of this study to determine prognosis of incidentally detected ambulatory atrial fibrillation (IA-AF) and its response to antithrombotic therapy. We performed a cohort study of 5,555 patients with IA-AF (mean age 70.9 ± 10.1, 38.4% female) and 24,705 ageand gender-matched controls without AF followed three years using UK Clinical Practice Research Datalink. We measured incidence rates of stroke, all-cause mortality, myocardial infarction, major bleeding, and effect of antithrombotic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 43 publications
2
91
1
5
Order By: Relevance
“…5 Most of the study monitor-detected AF was brief and subclinical, and may or may not have been causally related to the index stroke, but nevertheless represents a potentially treatable risk factor for recurrent stroke. 7,24,31,32 Increasing age is known to be associated with a greater likelihood of both clinical and subclinical AF, 4,33 but we found that age was not a significant predictor when APB count is included in the model. However, we did not study patients aged <55 years so the ability to fully assess the effect of age was limited.…”
Section: Gladstone Et Al Predicting Af In Cryptogenic Stroke 939contrasting
confidence: 55%
“…5 Most of the study monitor-detected AF was brief and subclinical, and may or may not have been causally related to the index stroke, but nevertheless represents a potentially treatable risk factor for recurrent stroke. 7,24,31,32 Increasing age is known to be associated with a greater likelihood of both clinical and subclinical AF, 4,33 but we found that age was not a significant predictor when APB count is included in the model. However, we did not study patients aged <55 years so the ability to fully assess the effect of age was limited.…”
Section: Gladstone Et Al Predicting Af In Cryptogenic Stroke 939contrasting
confidence: 55%
“…50 However, the relationship between AF burden and stroke risk is not fully established. In 28.6% of individuals with AF detected by intermittent ECGs, the diagnosis was made from 1 episode of AF, and 12 individuals presented with ≥2 episodes of AF <30 seconds, likely representing a low AF burden.…”
Section: Limitationsmentioning
confidence: 99%
“…AF oft en is asymptomatic, and only one in 12 paroxysms of AF are symptomatic. 32 Indeed, asymptomatic AF may carry a poor prognosis, 33 and symptoms are not a good guide to whether AF is present. 34 Associated comorbidities such as hypertension and heart failure need to be managed as part of a holistic approach to AF management.…”
mentioning
confidence: 99%